Campaign, counseling and compliance with influenza vaccine among older persons - Avelino-Silva, Vivian Iida (Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo, 2011)
OBJECTIVES: Population aging raises concerns regarding the increases in the rates of morbidity and mortality that result from influenza and its complications. Although vaccination is the most important tool for preventing influenza, vaccination program among high-risk groups has not reached its predetermined aims in several settings. This study aimed to evaluate the impacts of clinical and demographic factors on vaccine compliance among the elderly in a setting that includes a well-established annual national influenza vaccination campaign. METHODS: This cross-sectional study included 134 elderly patients who were regularly followed in an academic medical institution and who were evaluated for their influenza vaccination uptake within the last five years; in addition, the demographic and clinical characteristics and the reasons for compliance or noncompliance with the vaccination program were investigated. RESULTS: In total, 67.1% of the participants received the seasonal influenza vaccine in 2009. Within this vaccination-compliant group, the most common reason for vaccine uptake was the annual nationwide campaign (52.2%; 95% CI: 41.4–62.9%); compared to the noncompliant group, a higher percentage of compliant patients had been advised by their physician to take the vaccine (58.9% vs. 34.1%; p<0.01). CONCLUSION: The education of patients and health care professionals along with the implementation of immunization campaigns should be evaluated and considered by health authorities as essential for increasing the success rate of influenza vaccination compliance among the elderly.